Contrasting Proteomic Responses of Adult and Larval Coral to High Temperatures - McRae, Crystal J.; Mayfield, Anderson B.; Huang, Wen-Bin; Côté, Isabelle M.; Fan, Tung-Yung (Frontiers in Marine Science, 2021)
Climate change-induced increases in seawater temperature continue to impact coral reef ecosystems globally. There is a consequent need to characterize the responses of corals to thermal stress to understand the molecular processes underpinning these responses and identify hallmarks of resilience. Here we used an iTRAQ approach to compare the proteomes of adult corals (Pocillopora acuta) that had been thermally conditioned at a control (26°C) or elevated temperature (29.5°C) for three reproductive cycles, as well as the larvae released by these corals. We found that larvae responded more to high-temperature exposure at the protein level than their parents and that different proteins were affected between life stages; a single protein was up-regulated at high temperatures in both adults and their offspring, and its identity is currently unknown. Similarly, different cellular pathways were affected by high-temperature exposure between the coral hosts and their dinoflagellate endosymbionts; proteins involved in translation and protein trafficking were most likely to be affected by high-temperature exposure in the former, with photosynthesis being the most thermo-sensitive process in the latter. Collectively, these findings highlight the importance of considering both life stage and the composition of the coral holobiont when using molecular-scale data to model cellular processes associated with responses to future ocean warming.